Building Information Modelling and Quantity Surveying Practice - Olatunji, Oluwole; Sher, W.; Gu, N. (United Arab Emirates University, Faculty of Engineering, 2010)
The construction industry is widely acknowledged as unique and conservative. BuildingInformation Modeling (BIM) systems have the potential to revolutionize current practices and toautomate the measurement of quantities from construction drawings. However, there are fears thatsuch developments could threaten the viability of the quantity surveying profession. This studyexplores the relationship between BIM systems and the roles of quantity surveyors in theconstruction industry. We argue that BIM challenges traditional roles of quantity surveyors andtheir relevance to the construction industry. We recommend the development of revised curriculafor quantity surveyors and further research into standard systems of measurement.